Advertising in the UK and Nigeria - A Comparative Study - Usikalu, Motunrayo (2013)
The premise of this paper is to contribute to the existing data particularly on the matter of the impact cultural differences have on the strategies that are adopted by international businesses. It was found that existing literature does not broach this topic with particular reference to Nigeria (a West African country), and so, this research paper attempts to bridge this gap is made in order to ascertain the underlying patterns of business behaviour. It is found that generally, on a variety of cultural dimensions, these two nations differ, while on some cultural dimensions, they are rather similar. A further understanding of the standardisation vs. adaption debate was reached with reference to these country's advertisement campaigns.